2019
DOI: 10.2478/ttj-2019-0011
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Road Traffic Accidents Hotspots Areas Using GIS in Ethiopia: A Case Study of Hosanna Town

Abstract: Due to increasing human population and the number of vehicles, road traffic accident has significant influence on human life and economic development. In the present study, road traffic accident data of three years (2015-2017) were obtained from Hosanna Town Traffic Police Department, and Hosanna Town Transport Authority in Ethiopia. The Global Position System was used to know X, Y coordinates of the accident locations. Global Position System point data and accident data were added to road network data using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Fourteen grouping methods were found among the 42 studies evaluated (Table 3), highlighting the use of section split (SS) (Al-Omari et al, 2020;Greibe, 2003;Guerrero-Barbosa and Santiago-Palacio, 2016;Halim et al, 2018;Hayidso et al, 2019;Nguyen et al, 2016;Qu et al, 2019;Saha et al, 2020;Sugiyanto et al, 2017;Yan et al, 2019), kernel density estimation (KDE) (Hegyi et al, 2017;Le et al, 2020aLe et al, , 2020bPleerux, 2020;Shafabakhsh et al, 2017;Soltani and Askari, 2014;Xie and Yan, 2013), network kernel density estimation (NKDE) (Al-Aamri et al, 2021;Fan et al, 2018;Nie et al, 2015;Xie and Yan, 2008), spatial autocorrelation (SA) (Chance Scott et al, 2016;Steenberghen et al, 2011;Ulak et al, 2019), community census (CC) (Dong et al, 2016;Dumbaugh et al, 2010;Vaz et al, 2017), and cells (Cui and Xie, 2021;Debrabant et al, 2018;Geurts et al, 2005;Xiao et al, 2021). Less frequently used were beta-binomial screening (Park and Sahaji, 2013b), city limits , DBSCAN (Szénási and Jankó, 2017), the Firefly algorithm (Yuan et al, 2020), Gaussian mixture models (GMMs) (Mansourkhaki et al, 2017), nearest neighbor (NN) (Rahman et al, 2020)…”
Section: Grouping Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Fourteen grouping methods were found among the 42 studies evaluated (Table 3), highlighting the use of section split (SS) (Al-Omari et al, 2020;Greibe, 2003;Guerrero-Barbosa and Santiago-Palacio, 2016;Halim et al, 2018;Hayidso et al, 2019;Nguyen et al, 2016;Qu et al, 2019;Saha et al, 2020;Sugiyanto et al, 2017;Yan et al, 2019), kernel density estimation (KDE) (Hegyi et al, 2017;Le et al, 2020aLe et al, , 2020bPleerux, 2020;Shafabakhsh et al, 2017;Soltani and Askari, 2014;Xie and Yan, 2013), network kernel density estimation (NKDE) (Al-Aamri et al, 2021;Fan et al, 2018;Nie et al, 2015;Xie and Yan, 2008), spatial autocorrelation (SA) (Chance Scott et al, 2016;Steenberghen et al, 2011;Ulak et al, 2019), community census (CC) (Dong et al, 2016;Dumbaugh et al, 2010;Vaz et al, 2017), and cells (Cui and Xie, 2021;Debrabant et al, 2018;Geurts et al, 2005;Xiao et al, 2021). Less frequently used were beta-binomial screening (Park and Sahaji, 2013b), city limits , DBSCAN (Szénási and Jankó, 2017), the Firefly algorithm (Yuan et al, 2020), Gaussian mixture models (GMMs) (Mansourkhaki et al, 2017), nearest neighbor (NN) (Rahman et al, 2020)…”
Section: Grouping Methodsmentioning
confidence: 99%
“…The segments and junctions approach segregates roads and intersections into units of equal size and searches for accident distributions that characterize such units as APLs. Of the 12 studies identified that used segments and junctions, 11 applied previously fixed dimensions to identify specific segments and radii, in order to scan for RTAs (Al-Omari et al, 2020;Guerrero-Barbosa and Santiago-Palacio, 2016;Halim et al, 2018;Hayidso et al, 2019;Nguyen et al, 2016;Qu et al, 2019;Saha et al, 2020;Sugiyanto et al, 2017;Yan et al, 2019). Only one of the 12 studies used the beta-binomial approach to obtain UAs composed of segments and junctions (Park and Sahaji, 2013a).…”
Section: Units Of Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…This method selects the option closest to the ideal variation and farthest from the basal variation (the variant with the worst rating) assuming that all crite-ria have maximizing character. If not, it is necessary to convert all of the criteria [25][26][27][28]. The g ij elements are normalized according to the formula [29,30]:…”
Section: Variant Solution Selection Using Topsis Methodsmentioning
confidence: 99%